Malignant peripheral nerve sheath tumors of the sino-nasal tract: about an unusual case report. Issue 2 (18th February 2022) - Boujida, Ismail; Elouazzani, Hafsa; Derqaoui, Sabrine; Belghiti, Hicham; Sayad, Zahra; Boulaades, Malik; Zouaidia, Fouad; Cherradi, Nadia
Abstract: Malignant peripheral nerve sheath tumors are defined as malignant tumors arising from or differentiating toward the cells of the peripheral nerve sheath. They occur in about 8–16% within the head and neck region. Morphologically, some malignant tumors look like malignant peripheral nerve sheath tumors, particularly in the head and neck location; however, immunohistochemistry have a great contribution to distinguish between them. This case report is on a 45-year-old woman with a malignant peripheral nerve sheath tumor located in the sino-nasal tract.